PENGARUH PEMBERIAN TUNJANGAN KINERJA, KOMITMEN ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP KINERJA PERSONEL BRIMOB POLRI PADA SATUAN BRIMOB POLDA POLDA SULTRA - Risman R; Adnan Hakim; Muhammad Masri; Muhammad Taufik; Isalman Isalman (Pascasarjana Universitas Halu Oleo, 2021)
To determine and analyze the effect of providing performance allowances, organizational commitment and organizational citizenship behavior simultaneously and partially on the performance of Brimob Polri personnel at the Brimob Unit Polda Polda Sultra. The design in this study refers to the positivist paradigm with the approach used is quantitative. This type of research is explanatory research. The population in this study were Brimob Police personnel at the Southeast Sulawesi Police Mobile Brigade Unit, namely the ranks of BRIPKA and BRIGADIR, BRIPTU and BRIPDA and BHARATU, namely 594 Brimob Police personnel. In this study, the Slovin formula was used with a precision level of 10%, so the sample size was 86 respondents. The sampling technique used is purposive sampling. The analytical method used in this research is descriptive analysis and multivariate analysis using SPSS 22.0 statistical software. The provision of performance allowances, organizational commitment and organizational citizenship behavior simultaneously and partially has a positive and significant effect on the performance of Brimob personnel at the Southeast Sulawesi Police Mobile Brigade Unit. This means that any increase that occurs in the provision of performance allowances, organizational commitment and organizational citizenship behavior will have an impact on improving the performance of Brimob personnel at the Southeast Sulawesi Police Mobile Brigade Unit.